2004
DOI: 10.1007/s00330-004-2430-1
|View full text |Cite
|
Sign up to set email alerts
|

Spiral CT and multidetector-row CT diagnosis of perforation of the small intestine caused by ingested foreign bodies

Abstract: The aim of this retrospective study was to emphasize the performances of spiral CT (HCT) and multidetector-row CT (MDCT) as very effective imaging modalities for the diagnosis of intestinal perforations caused by calcified alimentary foreign bodies. Eight sites of perforations of the ileum by ingested foreign bodies were found in seven patients--one patient presenting with two separate sites of perforation. The diagnosis was successfully made by HCT in four patients and MDCT in the remaining three. Involuntari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
166
1
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(175 citation statements)
references
References 10 publications
1
166
1
7
Order By: Relevance
“…Thus, it is the first method of choice for evaluating patients with acute abdominal pain and for detecting foreign bodies. 3 US revealed minimal free fluid in the pelvic region of our case. Following this, abdominal CT with contrast agent revealed a typical image of the perforation caused by ingested fish bone.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…Thus, it is the first method of choice for evaluating patients with acute abdominal pain and for detecting foreign bodies. 3 US revealed minimal free fluid in the pelvic region of our case. Following this, abdominal CT with contrast agent revealed a typical image of the perforation caused by ingested fish bone.…”
Section: Discussionsupporting
confidence: 45%
“…12 Coulier et al also reported that perforation is most commonly observed at the angular regions like the distal portion of the ileum where lumen is narrow. 3 With our case, the perforation was at 15 cm proximal of the ileocecal valve. The perforation may seldom occur at regions like the hernia sac, Meckel diverticulum, and appendix.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…La tomografía confiere una mayor utilidad en casos específicos dado que puede descartar complicaciones como las perforaciones y abscesos. Adicionalmente, puede brindar mejor información sobre la localización del CE (intra o extraluminal) con el fin de determinar la conducta y, en caso de requerirlo, la vía de abordaje (20,21).…”
Section: Discussionunclassified
“…3 Even with a detailed clinical presentation, diagnosis may be difficult and delayed since the ingestion fish bones or other foreign bodies may not be mentioned in the history of the patient.…”
Section: Discussionmentioning
confidence: 99%